Organizational and Job Resources on Employees’ Job Insecurity During the First Wave of COVID-19: The Mediating Effect of Work Engagement - Vieira dos Santos, Joana; Gonçalves, Sónia P.; Silva, Isabel S.; Veloso, Ana; Moura, Rita; Brandão, Catarina (Frontiers in Psychology, 2022)
The world of work has been severely affected by the COVID-19 pandemic due to the high instability observed in the labor market, bringing several new challenges for leaders and employees. The present study aims to analyze the role of organizational and job resources in predicting employees’ job insecurity during the first wave of the COVID-19 outbreak, through the mediating role of work engagement. A sample of 207 Portuguese employees participated (Mean age = 45 years old, SD = 9.92), of which 64.7% were women. Data was collected using an online survey, including self-report measures of organizational resources (perceived organizational support), job resources (performance feedback and job autonomy), job insecurity, and work engagement. Data showed that job and organizational resources negatively influenced job insecurity. Moreover, work engagement was a significant mediator of the relation between performance feedback (facet of job resources) and job insecurity. Findings suggest that investing in job and organizational resources can act as protective factors to minimize feelings of job insecurity. Likewise, leaders should foster work engagement among employees to help them balance the relation between these resources and job insecurity, especially in crisis situations. Overall, this study takes a new, underexplored perspective, theoretically bridging organizational and job resources with job insecurity and work engagement during a time of great uncertainty, such as the COVID-19 pandemic.